PERSEPSI PETERNAK TERHADAP PENGUATAN SUBSISTEM AGRIBISNIS SAPI POTONG DAN MATERI PENYULUHAN BERDASARKAN PENDEKATAN SWOT ANALYSIS - Lina Anggraini; S Sunarto; Wahyu Windari (JURNAL GALUNG TROPIKA, 2019)
Beef management is currently directed to be based on agribusiness. Agribusiness has 4 subsystems that must be managed by farmers, namely the upstream subsystem, primary agriculture (cultivation), downstream, and supporting system. The aims of this study was to determine the agribusiness subsystems that were considered weak in Argosadono Gapoktan which was already based on animal husbandry agribusiness. Furthermore, to explore the ability of farmers to strengthen the agribusiness subsystem through counseling. The study was conducted in Ngampel Village, Papar District, Kediri Regency, East Java, Indonesia. The research approach used quantitative descriptive with Gapoktan Argosadono breeders object by involving their management as informants in this study. Sampling technique using purposive sampling with criteria for groups of livestock who joined the Gapoktan was an active group and recommended by the chairman of Gapoktan, has a complete core management, and has good communication skills. Data collection techniques used were observation, semistructured interviews, filling out closed questionnaires, Forum Group Discussion, and documentation. Data analysis techniques used SWOT analysis, counseling design, and continued evaluation of farmers' perceptions of the material that has been delivered in counseling. The results of the study based on the SWOT analysis diagram, obtained a suitable strategy in quadrant I (one), namely SO (Strengths-Opportunities). The strategy that must be implemented was to support an aggressive growth policy (Growth oriented strategy). The number of SO (Strengths-Opportunities) strategies obtained was 9 items, while the most pressing topic at the moment was the provision of cattle scales. Based on the 9 items of the SO strategy, the material was determined to support the running of the SO strategy. Based on the decision making matrix, the counseling material was obtained, namely the calculation of body weight using the Lambourne formula and the meter. After the implementation of counseling, perception evaluation carried out. The results obtained by farmers received very good innovation, as many as 47 respondents from 56 respondents were in the criterion V whose predicate perception was very good.